O normatywnej regulacji zachowań - Buczkowski, Piotr (Wydział Prawa i Administracji UAM, 1991)
The article attempts to formulate a typology of social order on the basis of the criterion of a normative regulation of behaviour. Two basic types of norms (patterns of behaviour) may be distinguished: norms-orders and norms-interdictions. From this point of view the author analyses and indicates the limitations of the typologies of social order formulated by S. Ossowski and K. R. Popper. The type of social order based on norms-orders, by determining detailed patterns of behaviour, limits individual activity, creativity and innovativeness. Free from the above shortcomings is the order based on norms-interdictions, for it leaves to individuals and social groups unregulated spheres, offering the possibilities of generating new patterns of behaviour. The proposed typology is an idealizational construct, and it requires to be concretized by taking into account other factors indicated by the analysed conceptions.
On normative regulation of behaviour